ANALISIS EFESIENSI PENGGUNAAN INVESTANSI TERHADAP (PDRB) PRODUK DOMESTIK REGIONAL BRUTO DI PROVINSI NUSA TENGGARA BARAT TAHUN 2015-2019 - Ni Ketut Desi Sustari; Muhamad Sayuti (Fakultas Ekonomi dan Bisnis Universitas Islam Al-Azhar Mataram, 2022)
This research is entitled “Efficiency Analysis of Investment Use of Gross Regional Domestic Product (GRDP) in West Nusa Tenggara Province in 2015-2019, which aims to determine the efficiency and development of investment in West Nusa Tenggara Province. This type of research is descriptive research, data collection method used is case study method with data collection techniques are documentation and interviews. The type of data used is the type of quantitative data. The data sources are secondary data (domestic private investment (PMDN) and foreign private investment (PMA) from 2015-2019 as well as GRDP (Gross Regional Domestic Product) of West Nusa Tenggara Province in 2015-2019. Based on the results of the discussion, it is concluded that the average The average ICOR value from 2015-2019 which is calculated using the average method shows the ICOR coefficient of 3.9 this shows that the average ICOR coefficient is still low or in the efficient category. this means that the investment utilization is right on target. And in 2017 ICOR was no exception in the inefficient category, where the highest ICOR occurred this year at 16.4 percent, this is because the use of investment in that year has not produced maximum output so that the output or results obtained are not optimal. produced is not in accordance with what has been sacrificed to produce the output, or maybe the expected output or results have not been produced in that year but will produce in the following year.